The key role of physical exercise in the prevention and treatment of osteoporosis - Karpińska, Anna; Łopatka, Patrycja; Wrzesiński, Bartłomiej; Piechocka, Edyta; Wojtczak, Paweł; Ziółkowska, Anna (Journal of Education, Health and Sport, 2018)
Osteoporosis is a commonly occurring condition that affects, mainly elderly people. Bone loss may be caused many factors, such as menopausal period, slender body structure, inappropriate diet, or genetic determinants. The systematic and properly performed physical activity is of a significant importance in the prevention and control of the disease symptoms. Beneficial results are obtained by implementation of exercises of the following types: strength, endurance, stretching and mixed efforts. Performing physical activity accurately results in lowering of the risk of early osteoporosis and reduces the intensity of bone degeneration processes by inhibiting and stimulating appropriate mechanisms within the bone tissue.